2023
DOI: 10.22541/essoar.167690082.29222366/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid basal channel growth beneath Greenland's longest floating ice shelf

Abstract: Nioghalvfjerdsfjorden Glacier (N79) is one of the two main outlets for Greenland’s largest ice stream, the Northeast Greenland Ice Stream (NEGIS), and is the more stable of the two, with no calving front retreat expected in the near future. Using a novel elevation reconstruction approach combining digital elevation models (DEMs) and laser altimetry, previously undetected local phenomena are identified complicating this assessment. N79 is found to have a complex network of basal channels that were largely stabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…Evidence of AIW has even been found in a marginal surface lake (Blåsø, Figure 1a) near the N79 grounding line (Bentley et al, 2022). This coincides with other glaciers in northern Greenland seeing an onset of widespread calving events over the last decade (Ochwat et al, 2022).Laser altimetry time series indicate a dynamic thinning of less than 0.5 m annually from 1999 to 2009 on N79 , with longer time series revealing an increased rate of thinning after 2012 near the center of the glacier close to the grounding line (Narkevic et al, 2020). However, this accelerated thinning is only observed in a few locations because of the sparse spatial coverage of airborne altimetry between 2009 and 2018 (Figure S2 in Supporting Information S1).…”
supporting
confidence: 70%
See 1 more Smart Citation
“…Evidence of AIW has even been found in a marginal surface lake (Blåsø, Figure 1a) near the N79 grounding line (Bentley et al, 2022). This coincides with other glaciers in northern Greenland seeing an onset of widespread calving events over the last decade (Ochwat et al, 2022).Laser altimetry time series indicate a dynamic thinning of less than 0.5 m annually from 1999 to 2009 on N79 , with longer time series revealing an increased rate of thinning after 2012 near the center of the glacier close to the grounding line (Narkevic et al, 2020). However, this accelerated thinning is only observed in a few locations because of the sparse spatial coverage of airborne altimetry between 2009 and 2018 (Figure S2 in Supporting Information S1).…”
supporting
confidence: 70%
“…Laser altimetry time series indicate a dynamic thinning of less than 0.5 m annually from 1999 to 2009 on N79 (Csatho et al., 2014), with longer time series revealing an increased rate of thinning after 2012 near the center of the glacier close to the grounding line (Narkevic et al., 2020). However, this accelerated thinning is only observed in a few locations because of the sparse spatial coverage of airborne altimetry between 2009 and 2018 (Figure S2 in Supporting Information ).…”
Section: Introductionmentioning
confidence: 99%
“…The lower rates of ice advection from upstream make RG more prone to developing deep channels. At 79N, it has been suggested that the recent expansion of its central basal channel is a consequence of heightened Q sg , attributed to a signiĄcantly expanded surface melt area during summer, brought about by atmospheric warming (Narkevic et al, 2023;Zeising et al, 2023). Moreover, the extensive network of moulins observed along the GrIS margins in summer (Turton et al, 2021;Ehrenfeucht et al, 2023;Rawlins et al, 2023), coupled with expected increases in surface melt on the GrIS in a warmer climate (Aschwanden et al, 2019;Muntjewerf et al, 2020), are likely to yield end-of-century discharge estimates at these sites that are comparable to those of Petermann (see projected runoff for the northern, northeastern and northwestern GrIS sectors in Slater et al…”
Section: (G))mentioning
confidence: 99%
“…In addition to erosion, because many outlet glaciers approach floatation toward their margins, sediment may preferentially deposit close to the terminus creating a moraine (sometimes called a sill in the literature), which also shapes the topography at termini (Figure 2; Batchelor and others, 2018). Comparisons of BedMachine to radar-derived topography in outlet glaciers reveals that there may be a systematic offset of the bed elevation between the two but that the radar-derived bed slopes are well-preserved in BedMachine (Morlighem and others, 2017;Catania and others, 2018;Narkevic and Anton, 2023). In addition, BedMachine is unrealistically smooth at small scales making it less useful for examining subglacial water routing and the influence of small-scale bed features on dynamics (MacKie and others, 2021).…”
Section: Topography Observations For Greenlandmentioning
confidence: 99%